Work concepts for the future : managing alternative work arrangements - Estess, Patricia Schiff (Crisp Pub. Menlo ParkUS, 1996)
Focuses on 10 alternative work arrangements (AWA), including: flex time, compressed work weeks, and voluntary reduced work time. Shows the benefits of AWA from the point of view both of the employee and of the manager. Provides guidelines for managing the performance of individuals, as well as a department on AWA.